Bridging the Gap: Hong Kong Senior Civil Servants and the 1966 Riots. Issue 1 (2nd January 2017) - Scott, Ian
ABSTRACT: The 1966 Hong Kong riots were the trigger for wide-ranging changes in relationships between the government and the public which shaped the political future of the colony. However, it is not immediately clear why a relatively small-scale disturbance which was quickly contained should have had such a considerable impact. The explanation, it is argued, lies in a confluence of factors. The riots were the first to be specifically concerned with events in Hong Kong rather than in China and therefore required attention to local causes; urban councillors were demanding more electoral representation and devolution of government functions to the Council; the Commission of Inquiry into the riots held public meetings raising political awareness; and reforming senior civil servants saw the riots as an opportunity for change. Because there was antipathy within government towards elections and to any devolution of functions, the recommendations of the Commission of Inquiry were given priority, resulting in administrative rather than public policy or electoral solutions, a decision which retarded the development of democracy.